Market Wages and Youth Crime - Grogger, Jeff (Journal of Labor Economics, 1998)
To study the problem of widespread youth crime, the author analyzes a time-allocation model in which consumers face parametric wages and diminishing marginal returns to crime. The theory motivates an econometric model that he estimates using data from the National Longitudinal Survey of Youth. The author's estimates suggest that youth behavior is responsive to price incentives and that falling real wages may have been an important determinant of rising youth crime during the 1970s and 1980s. Moreover, wage differentials explain a substantial component of both the racial differential in criminal participation and the age distribution of crime. Copyright 1998 by University of Chicago Press.